A Review of the Book: “Field Archaeology (Systematic Principals in Excavation) - Mohamad ghomrifatideh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Most of the archaeological information should be gained from the examination and study of the past human societies. This information is usually obtained from the archaeological fieldworks that are divided into two main categories: surface survey and excavation. Since all of the antiquities are endangered in one way or another, all surface evidence should be recorded carefully. On the other hand, excavation is destructive in nature, so nothing would return to its original position after the fulfilment of an excavation. Therefore, taking the maximum information out of the archaeological deposits needs maximum accuracy, and to gain this goal, archaeologists must use scientific principles. These principles are taught to students under a course entitled “Methods of Excavation and Surface Survey in Archaeology”. The book under review in this paper deals with such topics.